2012
DOI: 10.1149/1.3700888
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Gap-Fill Strategy for 28 nm Shallow Trench Isolation

Abstract: At the 28 nm technology node, the conventional Shallow Trench Isolation (STI) gap-fill process shows some filling limitations due to voids formation in the oxide layer (SiO 2 ), leading to electrical isolation trouble. In this paper, a new gap-fill strategy called L-E-G (for Liner -Etch-back -Gap-fill) is presented. This strategy is based on an innovative etch-back step, using downstream plasma, which allows liner profile reshaping and improves the slope in trenches. First, the etch-back process on blanket waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…We use 300 mm diameter Czochralsky (CZ)-grown Silicon (001) wafers, sliced from the ingot with a slight 0.15° miscut angle towards either the [110] or [100] direction. Prior to the H2 annealing, the native oxide is removed by SICONI TM process 35 . After transferring the wafers under vacuum, the H2 annealing is performed directly in a 300 mm Applied Materials MOCVD reactor specifically designed for III-V materials growth and which uses purified H2 as carrier gas.…”
mentioning
confidence: 99%
“…We use 300 mm diameter Czochralsky (CZ)-grown Silicon (001) wafers, sliced from the ingot with a slight 0.15° miscut angle towards either the [110] or [100] direction. Prior to the H2 annealing, the native oxide is removed by SICONI TM process 35 . After transferring the wafers under vacuum, the H2 annealing is performed directly in a 300 mm Applied Materials MOCVD reactor specifically designed for III-V materials growth and which uses purified H2 as carrier gas.…”
mentioning
confidence: 99%
“…It is suggested that NH 4 F and HF reactants are formed in the NH 3 /NF 3 remote plasma chamber by NF 3 (respectively NH 3 ) dissociation into NF x (x = 1-2) and F [respectively NH x (x = 1-2) and H] and subsequent recombination of these fragments together and with the feed gases, as described by Eqs. ( 2)-( 5), 17,[23][24][25]…”
Section: Discussion On the Etching Mechanisms Of Si 3 N 4 Films Exposed To Nh 3 /Nf 3 Remote Plasmamentioning
confidence: 99%
“…It has already been reported that the etching of Si 3 N 4 or SiO 2 films exposed to NH 3 /NF 3 remote plasma proceeds with the formation of an ammonium hexafluorosilicate (NH 4 ) 2 SiF 6 salt layer on their surface. 17,[23][24][25] Figures 2(a) and 2(b) show the scanning electronic microscopy (SEM) and atomic force microscopy (AFM) images of the salt layer formed on a Si 3 N 4 film exposed to the NH 3 /NF 3 RP process at 60 °C. It looks like a tangle of polycrystals separated with cracks and voids.…”
Section: Kinetic Ellipsometrymentioning
confidence: 99%
“…This assumption was tested with a 600 Torr/ 900°C/10 min H 2 annealing of different on-axis Si(001) wafers. Prior to the H 2 annealing, the native oxide is removed by SICONI™ process [14]. Atomic force microscopy (AFM) images of Figure 4a.…”
Section: Ball-and-stick Model Of Iii-v-on-si With {110} and {111}-apbmentioning
confidence: 99%